Beyond the Binary: Hymnographic Constructions of Eastern Orthodox Gender Identities - Purpura, Ashley M. (The journal of religion, 2017)
The article examines the gender identities in Orthodox hymnography. Topics include the failure of Orthodox hymnography to corelate gender identities with male-or female-sexed bodies, the tendency to negate the validity of gender identities, and Orthodox feminist theology. Also discussed are the concept of gender, Orthodox history, and liturgical hymns.